Health Education Intervention on Hand Washing in a selected Primary School Children - Farzan, MSA; Zerin, I; Kabir, MA; Pavel, MSR; Hossain, MS (Bangladesh Journal of Dental Research & Education, 2013)
DOI: http://dx.doi.org/10.3329/bjdre.v2i1.15571 Bangladesh Journal of Dental Research & Education Vol.2(1) 2012: 7-11